Mendidik lewat laut : makna etnopendagogik dalam tradisi Larung sesaji Probolinggo Jawa Timur - Septi Siti Ramadhani; Nabilla Larasati Rizkya Layana; Rella Gina Sonia; Siti Komariah; Mirna Nur Alia Abdullah (Sapientia Humana: Jurnal Sosial Humaniora, 2025)
Abstract The Larung Sesaji ritual in Probolinggo City is a coastal community tradition rich in symbolic meaning and social values. This ritual not only serves as an expression of gratitude for the blessings of nature but also functions as a medium of cultural preservation, education, and spiritual communication between humans, nature, and the Creator. This study aims to explore the symbolic meanings, social values, and educational functions embedded in the Larung Sesaji Bumi ritual and its relevance to the concept of ethnopedagogy. The research employed a qualitative descriptive approach using literature study methods, by analyzing academic sources such as journals, books, and related documents without conducting direct field observation. The results show that Larung Sesaji contains strong religious, social, ecological, and aesthetic values. The symbols within the offerings reflect the harmonious relationship between humans and nature, while collective participation in the ritual preparation and performance demonstrates social solidarity and mutual cooperation. Beyond its spiritual aspects, the ritual also holds educational significance as a medium for character education based on local wisdom. In the context of ethnopedagogy, Larung Sesaji Bumi serves as an effective cultural medium for cultivating religiosity, social responsibility, and cultural awareness among the community. Abstrak Ritual Larung Sesaji di Kota Probolinggo merupakan tradisi masyarakat pesisir yang sarat makna simbolik dan nilai sosial. Tradisi ini tidak hanya berfungsi sebagai ungkapan rasa syukur atas hasil bumi, tetapi juga sebagai sarana pelestarian budaya, media pendidikan, dan wujud komunikasi spiritual antara manusia, alam, serta Sang Pencipta. Penelitian ini bertujuan untuk mengungkap makna simbolik, nilai sosial, dan fungsi edukatif yang terkandung dalam ritual Larung Sesaji serta relevansinya dengan konsep etnopedagogik. Metode yang digunakan ialah pendekatan kualitatif deskriptif dengan teknik studi pustaka, yaitu menelaah berbagai sumber ilmiah seperti jurnal, buku, dan dokumen terkait tanpa melakukan observasi langsung ke lapangan. Hasil kajian menunjukkan bahwa Larung Sesaji Bumi memiliki nilai-nilai religius, sosial, ekologis, dan estetis yang tinggi. Simbol-simbol dalam sesaji menggambarkan hubungan harmonis antara manusia dan alam, sedangkan partisipasi masyarakat dalam persiapan dan pelaksanaan upacara mencerminkan semangat gotong royong serta solidaritas sosial. Selain berfungsi spiritual, tradisi ini juga memiliki nilai edukatif, yakni sebagai media pembelajaran karakter berbasis kearifan lokal. Dalam konteks etnopedagogik, Larung Sesaji Bumi menjadi sarana efektif dalam menanamkan nilai religiusitas, tanggung jawab sosial, dan rasa cinta budaya.